Detection and phylogenetic analysis of contemporary H14N2 Avian influenza A virus in domestic ducks in Southeast Asia (Cambodia) - Jurre Y. Siegers; Michelle Wille; Sokhoun Yann; Songha Tok; Sarath Sin; Sokha Chea; Alice Porco; Sreyem Sours; Vutha Chim; Samban Chea; Kimtuo Chhel; Sothyra Tum; et al. (Emerging Microbes and Infections, 2024)
Avian influenza virus (AIV) in Asia is a complex system with numerous subtypes and a highly porous wild birds-poultry interface. Certain AIV subtypes, such as H14, are underrepresented in current surveillance efforts, leaving gaps in our understanding of their ecology and evolution. The detection of rare subtype H14 in domestic ducks in Southeast Asia comprises a geographic region and domestic bird population previously unassociated with this subtype. These H14 viruses have a complex evolutionary history involving gene reassortment events. They share sequence similarity to AIVs endemic in Cambodian ducks, and Eurasian low pathogenicity and high pathogenicity H5Nx AIVs. The detection of these H14 viruses in Southeast Asian domestic poultry further advances our knowledge of the ecology and evolution of this subtype and reinforces the need for continued, longitudinal, active surveillance in domestic and wild birds. Additionally, in vivo and in vitro risk assessment should encompass rare AIV subtypes, as they have the potential to establish in poultry systems.